2009
DOI: 10.1007/s11596-009-0615-1
|View full text |Cite
|
Sign up to set email alerts
|

The single needle method for urethrovesical anastomosis with strengthened posterior fixation during laparoscopic radical prostatectomy

Abstract: The single needle method for urethrovesical anastomosis with strengthened posterior fixation during laparoscopic radical prostatectomy was explored. The method was initiated by performing a fixing suture with a knot at 4 o'clock of the posterior lip of bladder neck, and another suture at nearby position was performed to leave the knot outside. From 5 o'clock to 8 o'clock, sutures were performed every one o'clock to secure posterior approximation, then every two o'clock a suture. To avoid a loose anastomosis, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A 12-F Foley catheter was placed through the urethra by an assistant to identify the urethral lumen. UVA was performed with a running suture, as previously described [7]. Once all suture procedures were completed, the anastomotic stoma was cut off and checked extracorporeally.…”
Section: Methodsmentioning
confidence: 99%
“…A 12-F Foley catheter was placed through the urethra by an assistant to identify the urethral lumen. UVA was performed with a running suture, as previously described [7]. Once all suture procedures were completed, the anastomotic stoma was cut off and checked extracorporeally.…”
Section: Methodsmentioning
confidence: 99%
“…Upon increasing experience, temporary urinary leakage seldom occurred. The details of SNM and initial results compared with the results of several other methods of urethrovesical anastomosis that have been published (4). A short median time for anastomosis, a short median placement time of the retropubic drain, no postoperative persistent urinary leakage and no anastomotic stricture indicated that SNM was a simple and efficient method.…”
Section: Discussionmentioning
confidence: 99%
“…Between March 2005 and March 2010, we performed 329 cases of extraperitoneal laparoscopic radical prostatectomy (ELRP) with running urethrovesical anastomosis using the single needle method (4). In this study, we evaluated the oncological and clinical results after ELRP.…”
Section: Introductionmentioning
confidence: 99%
“…A running urethrovesical anastomosis using a 25-cm, 2-zero Monocryl suture with a UR-6 tape needle (Ethicon Inc.) was Bilateral intrafascial and interfascial nerve-sparing techniques T Zheng et al 514 performed. 12 To test the integrity of the urinary reconstruction, the bladder was filled with 200 ml saline. Any saline extravasation identified during this manoeuvre could be controlled with additional interrupted stitches.…”
Section: Surgical Techniquementioning
confidence: 99%